Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1590/1980-5373-mr-2020-0252
|View full text |Cite
|
Sign up to set email alerts
|

Dilatometric Cycles in the Study of Precipitation of Intermetallic Phases in Duplex Stainless Steels

Abstract: Duplex stainless steels (DSS) are used in offshore platforms due to their good properties resulting from the combination of two phases, namely austenite and ferrite. Secondary intermetallic phases, such as alpha prime (α´) and sigma (σ), which are harmful, can be formed at temperatures above 400 °C, or by a casting process. This study investigates the formation of sigma phase by thermal cycles running in a dilatometer (800 °C, 850 °C, 900 °C and 1,000 °C) for 1h, and at 850 °C for 3h and 7h. The optical micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The presence of the σ phase and γ 2 austenite was associated with the eutectoid decomposition of the ferrite into the σ phase and secondary austenite (γ 2 ) [ 36 ]. The examinations that were carried out with a ferritoscope confirmed the drop in ferrite content along with the extension of the holding times at both temperatures ( Figure 4 ); thus, it was shown that extending the holding time from 1 to 3 h was the main factor that reduced the content of the magnetic phase (i.e., ferrite, at 750 °C and 900 °C) and promoted the formation of non-magnetic σ phase [ 37 ]. The obtained results demonstrated that in the manufacture of DSS steel castings, it is necessary to accelerate the casting cooling process in the mould.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the σ phase and γ 2 austenite was associated with the eutectoid decomposition of the ferrite into the σ phase and secondary austenite (γ 2 ) [ 36 ]. The examinations that were carried out with a ferritoscope confirmed the drop in ferrite content along with the extension of the holding times at both temperatures ( Figure 4 ); thus, it was shown that extending the holding time from 1 to 3 h was the main factor that reduced the content of the magnetic phase (i.e., ferrite, at 750 °C and 900 °C) and promoted the formation of non-magnetic σ phase [ 37 ]. The obtained results demonstrated that in the manufacture of DSS steel castings, it is necessary to accelerate the casting cooling process in the mould.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the use of deep etching on the cast steel allowed for confirming the presence of the secondary austenite (γ 2 ) with the Widmanstätten morphology in the SEM-EDS studies ( Figure 10 ). The SEM-EDS analysis of the chemical composition of the austenite and secondary austenite (γ 2 ) showed that the secondary austenite contained lower content of Cr and Mo and a slightly higher content of Ni ( Table 3 ) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%